The impact of climate change on the Arctic - Tsetsos, Konstantinos (Metis Institute for Strategy and Foresight, Bundeswehr University Munich, 2018)
The impact of climate change on the Arctic is of importance to Germany and the international community in geopolitical, geoeconomic and geoecological terms. The freedom of sea routes, the use of maritime resources and the exploitation of these resources on the sea bed and the possible militarisation of the Arctic will affect German and European economic and security interests. Although the security policy implications of climate change will emerge only gradually, Germany should prepare for political, legal, economic, ecological and military challenges in concert with its European and international partners. These include establishing capabilities for operations in the Arctic and conducting manoeuvres with partners in the region.